A nanotechnology based new approach for chemotherapy of Cutaneous Leishmaniasis: TIO2@AG nanoparticles - Nigella sativa oil combinations - Abamor, Emrah Sefik; Allahverdiyev, Adil M. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2016)
Since toxicity and resistance are the major drawbacks of current antileishmanial drugs, studies have been recently focused on combination therapy in fight against leishmaniasis. Combination therapy generally provides opportunity to decrease toxicity of applied agents and enhance their antimicrobial performance. Moreover, this method can be effective in preventing drug resistance. Highly antileishmanial effects of silver doped titanium dioxide nanoparticles (TiAgNps) and Nigella sativa oil were demonstrated in previous studies. However, toxicity is still an important factor preventing use of these molecules in clinic. By considering high antileishmanial potential of each agent and basic principles of combination therapy, we propose that use of combinations including non-toxic concentrations of TiAgNps and N. sativa oil may compose more effective and safer formulations against Leishmania parasites. Therefore, the main goal of the present study was to investigate antileishmanial effects of non-toxic concentrations of TiAgNps and Nigella sativa oil combinations on promastigote and amastigote-macrophage culture systems and also to develop nanotechnology based new antileishmanial strategies against Cutaneous Leishmaniasis. Numerous parameters such as proliferation, metabolic activity, apoptosis, amastigote-promastigote conversion, infection index analysis and nitric oxide production were used to detect antileishmanial efficacies of combinations. Investigated all parameters demonstrated that TiAgNps-N. sativa oil combinations had significant antileishmanial effect on each life forms of parasites. Tested combinations were found to decrease proliferation rates of Leishmania tropica promastigotes in a range between 1,5-25 folds and metabolic activity values between 2 and 4 folds indicating that combination applications lead to virtually inhibition of promastigotes and elimination of parasites were directly related to apoptosis manner. TiAgNps-N. sativa combinations also demonstrated killing effects on L. tropica amastigotes by decreasing infection index values of macrophages 5-20 folds, inhibiting their metabolic activities up to 5 fold, preventing amastigote-promastigote conversion and producing high amounts of nitric oxide. All these results emphasize high potential of TiAgNps-N. sativa oil combinations as new, safer and effective antileishmanial formulations against Cutaneous Leishmaniasis. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Leishmania; Cutaneous; Leishmaniasis; Nanotechnology; Titanium; Silver; Nanoparticles; Nigella sativa; ANTIBACTERIAL ACTIVITY; ANTIMICROBIAL ACTIVITY; VISCERAL LEISHMANIASIS; DIOXIDE NANOPARTICLES; SILVER NANOPARTICLES; TITANIUM-DIOXIDE; ANTIMONY; THERAPY; THYMOQUINONE; ANTIBIOTICS; Parasitology